Des « origines » du « devoir de mémoire » aux sources de la mémoire de la Shoah : historiciser la mémoire de son oubli - Sébastien Ledoux (Les Cahiers de Framespa)
The article gives an overview of a research project dedicated to the history of the expression « devoir de mémoire » (“duty to remember”) and how it was challenged by the unexpected discovery of early sources pertaining to the first memory of the Holocaust. Contradicting the dominant historiographical discourse that focused on forgetting, these sources led to a double historicization: of Holocaust memory, on the one hand, and, on the other, of the relationship between memory and forgetting which, spearheaded by Holocaust memory, has been rethought through much broader political and social perspectives concerning the past violence since 1980’s.